Social-Cultural Approach to Modeling of Educational Process under the Conditions of Multinational Society - Elvira Zaredinova; Evelina Bakshysh (Pedagogical Discourse, 2012)
The article deals with the problem of a socio-cultural approach. Formation of a personality is considered in a context of universal culture taking into account specific cultural conditions of a person’s activity; the content of education is defined at the level of modern world culture.The main ways of realization are revealed of social-cultural approach as an important stage of teaching modeling and educational process under the conditions of multinational society.